2014
DOI: 10.1007/s40519-014-0167-7
|View full text |Cite
|
Sign up to set email alerts
|

Superstition predicts favorable weight change in an open-placebo trial: a prospective study

Abstract: Given the difficulty of losing weight via adhering to healthy lifestyle choices, this study sought to understand how a placebo may elicit favorable weight change. Specifically, we examined if superstition may be related to increased responsiveness to an open-placebo. In this pilot study of 25 undergraduate participants, it was hypothesized that individuals with higher levels of superstition may be more responsive to a 3-week open-placebo weight change trial. Participants were given once-daily saltine crackers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It is imperative to appreciate the personality characteristics that interact with several situational factors at any given time to determine the use and possibly even the efficacy of superstitious behavior in sports. Whether superstitions lead to a desired result via a placebo effect is not clear, but recent research evidence revealed that superstition and the placebo effect are strongly correlated and share almost 25% of the common variance (Rekhviashvili & Gupta, ). There are few differences in superstitious behaviors between athletes and non‐athletes, which could be observed in the quality and spectrum rather than the quantity of superstitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative to appreciate the personality characteristics that interact with several situational factors at any given time to determine the use and possibly even the efficacy of superstitious behavior in sports. Whether superstitions lead to a desired result via a placebo effect is not clear, but recent research evidence revealed that superstition and the placebo effect are strongly correlated and share almost 25% of the common variance (Rekhviashvili & Gupta, ). There are few differences in superstitious behaviors between athletes and non‐athletes, which could be observed in the quality and spectrum rather than the quantity of superstitions.…”
Section: Discussionmentioning
confidence: 99%
“…The placebo mechanism in performance situations may trigger greater persistence on a given task that in turn may enhance self‐efficacy, which can lead to better performance, as revealed in a series of experimental studies (Damisch et al ., ). Recent research shows that the placebo effect and acts of superstition share 25% of common variance (Rekhviashvili & Gupta, ).…”
Section: Reasons Behind Superstitious Behavior In Sportmentioning
confidence: 99%
“…The mechanism behind the independent effect of superstition and the placebo effect on performance regulation is similar; the human belief system or expectancy mediates the effect. Moreover, superstition is associated with plasticity of cognition (Rekhviashvili and Gupta 2015). The present study aimed to explore the role superstition plays in the placebo effect on memory performance.…”
Section: The Placebo Effect and Its Relationship With Superstitionmentioning
confidence: 94%
“…The resulting improvement in performance could be due to the involved placebo effect. Another study showed that superstition through the use of placebos can have an impact on favourable weight change (Rekhviashvili and Gupta 2015). The study found that people who are more superstitious are more responsive to a placebo because they believe in the positive impact of the placebo on the desired weight change.…”
Section: The Placebo Effect and Its Relationship With Superstitionmentioning
confidence: 99%
See 1 more Smart Citation